Concussion Recovery in Children and Adolescents: A Retrospective Study. Issue 12 (21st December 2022) - Ferderber, Megan Lynn; Rizk, Christina; Zsoldos, Shellie; Meardon, Stacey; Lin, Chia-Cheng
Background: Concussion is a common injury among children and adolescents, with a growing body of literature supporting a variety of diagnostic and treatment modalities. Recovery is variable and depends on multiple factors that can be evaluated through a clinic visit: a thorough history, physical examination, and use of the Post-concussion Symptom Scale (PCSS). Purpose/Hypothesis: The purpose of this study was to evaluate factors associated with overall recovery from concussion in children and adolescents in the clinical setting. It was hypothesized that the presence of 1 of a number of pre- or postinjury characteristics will be associated with poor concussion recovery. Study Design: Case-control study; Level of evidence, 3. Methods: We conducted a retrospective chart review of adolescents and children aged 6 to 17 years with a diagnosis of concussion who were evaluated at a single sports medicine center between January 2015 and December 2019. Cases were categorized into recovered (PCSS <7) and poorly recovered (PCSS ≥7) cohorts based on the last PCSS scores during clinical follow-ups for concussion management. Results: Of the 162 charts reviewed, 110 cases met inclusion criteria. Significant statistical differences were found between the recovered and poorly recovered cohorts regarding mean days from injury to last clinic visit, previous migraine diagnosis, and emergency room (ER) visit before the first clinic visit ( P < .01 for all). Binary logistic regression analysis revealed that the most predictive factors associated with poorer recovery were having an ER visit before the first clinic evaluation ( P = .01) and previous migraine diagnosis ( P = .04). Conclusion: While many factors may contribute to overall recovery from concussion in pediatric populations, our study suggested that a history of migraine and an ER visit before clinic evaluation may be associated with poor recovery of concussive symptoms.